PENGARUH MOTIVASI EKONOMI, PENGETAHUAN TENTANG PAJAK, DAN PERTIMBANGAN PASAR TERHADAP KEPUTUSAN MAHASISWA PRODI AKUNTANSI UNTUK BERKARIER DI BIDANG PERPAJAKAN - Djoko Kristianto; Suharno Suharno (Universitas Slamet Riyadi, 2021)
The purpose of this research is to determine the effect of economic motivation, knowledge of taxes, and market considerations on careers in taxation. The development of the business world is progressing rapidly from time to time, resulting in growth and development of career opportunities or professions in various fields of work. Professions in the field of taxation such as being an employee of the directorate general of tax, tax consultant, have a special appeal among the public, because a person who has a career in taxation is considered a profession that has a high social strata by the community. This can make students have a high interest in a career in taxation after graduating. A student in planning his career certainly has considerations or influencing factors in determining which profession to choose. This research was conducted at the faculty of economics, Slamet Riyadi University Surakarta, with 92 accounting study program students who had passed the taxation course in semester 5 and 7. The results showed that, economic motivation has an effect on careers in the field of taxation, labor market considerations have an effect on careers in the field of taxation, while knowledge of taxes does not affect career considerations in taxation. with respondents from accounting study programs who have passed the taxation course in semester 5 and 7 as many as 92 students. The results showed that, economic motivation has an effect on careers in the field of taxation, labor market considerations have an effect on careers in the field of taxation, while knowledge of taxes does not affect career considerations in taxation. with respondents from accounting study programs who have passed the taxation course in semester 5 and 7 as many as 92 students. The results showed that, economic motivation has an effect on careers in the field of taxation, labor market considerations have an effect on careers in the field of taxation, while knowledge of taxes does not affect career considerations in taxation.